Akibat Hukum Cacat Formil dan Cacat Materiil pada Akta Notaris dalam Pembuktian Hukum di Indonesia - M. Adli Afriansyah; Rosmidah Rosmidah; Syamsir Syamsir (LPPM Institut Pendidikan Nusantara Global, 2026)
Notarial deeds are a crucial legal instrument in the civil litigation system in Indonesia. The authenticity of a deed depends not only on the proper procedural creation but also on the substance contained within it. This research aims to analyze the legal consequences of formal and material defects in notarial deeds concerning their validity, evidentiary power, and status in civil litigation cases. The main focus of this study is to identify the impact of formal defects, such as non-compliance with procedural requirements, and material defects, which relate to the inconsistency of the deed’s substance with legal facts. The research uses a normative legal methodology, employing legislative, conceptual, and case approaches. The study analyzes court decisions related to formal and material defects in notarial deeds, such as the South Jakarta District Court Decision No. 235/Pdt.G/2013 and the Surabaya District Court Decision No. 157/Pdt.G/2017, to understand the application of the law in practice. The findings show that violations of formal requirements may cause the deed to lose its authentic evidentiary value, while material defects may lead to the annulment of the deed. Therefore, it is essential for notaries to ensure compliance with both formal and material requirements when creating deeds to maintain legal certainty and prevent potential disputes. This study contributes to the understanding of the notary’s role and the impact of defects on the authenticity of deeds in civil law.